A potentiometric indirect uric acid sensor based on ZnO nanoflakes and immobilized uricase - Syed Muhammad, Usman Ali, Dr.; Zafar Hussain, Ibupoto; Muhammad, Kashif; Uda, Hashim, Prof. Dr.; Willander, Magnus (MDPI, 2013)
Link to publisher's homepage at http://www.mdpi.com/